2022
DOI: 10.1186/s40168-022-01300-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic exposure prevents acquisition of beneficial metabolic functions in the preterm infant gut microbiome

Abstract: Background Aberrations in the preterm microbiome following antibiotic therapy have been reported in previous studies. The objective of this study was to probe potential underlying mechanisms between this observation and susceptibility to adverse prematurity-related outcomes. Results Metagenomic shotgun sequencing was performed on 133 stool and 253 skin samples collected at 1 and 3 weeks of age from 68 infants born at <36 weeks postmenstrual age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In another study, gut colonization of mice with the symbiotic bacteria Bacteroides fragilis was found to mediate establishment of proper Th1/Th2 balance through bacterial surface polysaccharide A (62). Disruptions to this normal process of gut colonization with commensalssuch as with early antibiotic usecan thus lead to a dysfunctional gut mucosa predisposed to NEC(64)(65)(66). This hypothesis is supported by the mouse model by Chaaban et al (50) where exposure of newborn pups to 10 days of antibiotics resulted in several impairments to gut mucosal barrier, intestinal permeability, intestinal stem cell proliferation, and Paneth cell function.…”
mentioning
confidence: 94%
“…In another study, gut colonization of mice with the symbiotic bacteria Bacteroides fragilis was found to mediate establishment of proper Th1/Th2 balance through bacterial surface polysaccharide A (62). Disruptions to this normal process of gut colonization with commensalssuch as with early antibiotic usecan thus lead to a dysfunctional gut mucosa predisposed to NEC(64)(65)(66). This hypothesis is supported by the mouse model by Chaaban et al (50) where exposure of newborn pups to 10 days of antibiotics resulted in several impairments to gut mucosal barrier, intestinal permeability, intestinal stem cell proliferation, and Paneth cell function.…”
mentioning
confidence: 94%
“…Saleem et al [ 24 ] have demonstrated that the longer the duration of antibiotic use in preterm infants, the greater the delay in their feeding. Many scholars now believe that early antibiotic use in VLBW infants can lead to intestinal flora dysbiosis [ 25 , 26 ], which increases the risk of adverse outcomes such as NEC [ 27 ], prolongs the length of hospitalization, and increases the medical costs in preterm infants. In this study, the time to reach full enteral nutrition was also reduced significantly over the initial 3 years of the study period, suggesting that shortening the duration of early empirical antibiotic therapy may facilitate the establishment of normal intestinal flora and therefore decrease the time to reach full enteral feeds, and subsequently the incidence of LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Difference in species abundance between individuals with normal vs elevated L:R were identified with shrinkage linear discriminant analysis. 67 Significance of the association was tested using Wilcoxon rank sum. Examination of clinical covariates with microbial abundance was performed using zero inflated negative binomial generalized linear mixed models (ZINB-GLMM 68 ) using the “glmer” command from the lme4 package in R and performed nonparametric tests (Mann-Whitney U test or Kruskal-Wallis test), followed by Bonferroni correction for multiple testing.…”
Section: Methodsmentioning
confidence: 99%